APLIKASI EFEK GAYA APUNG DENGAN MOMEN PEMBALIK PADA MODEL TANGKI RANCANGAN UNTUK MENGHEMAT KONSUMSI DAYA POMPA PADA SISI DISCHARGE - Galbi, Mohammad; A, Ishak (Bina Teknika, 2016)
The use of the tank as well as a container or tank of liquid reserves to make use of the tank as a necessity. By using its own tank design model which is technically very possible to make the pressure in the tank is less than atmospheric pressure so that the tank will take some role pump connected in series are used for the purpose of improving high pressure. Thus the pressure in the tank is smaller than the atmospheric pressure is only generated from the process flow itself will save pump power required on the press. To prevent the air pressure in the tank exceeds the atmospheric pressure relief valve on the tank supplied air to the atmosphere. The more water into the tank, the greater the downward thrust force due to the weight of water and by the buoy to the piston in fixed position, the tank will move downward relative to the piston. The pressure in the tank due to the movement of the closed tube will follow the phenomenon of negative pressure. To get a larger volume of air or spring difleksi rate greater then the pole float should be as light as possible and frictional forces as small as possible.The goal is to produce a prototype tank that can lighten the pump working in particular on the discharge side so it can be input pump power savings. The calculations show that a high hit on the side of the press can be reduced upto 100 percent even including reducing losses on the discharge side by enlarging the capacity of the tank. Thus happen electricity savings of the power required on the discharge side of the pump to drain the water into the tank. With spring replacement inverting the inversion moment will produce a higher pressure suction force behind the rise of the spring.